Strategies for Choosing Investments in Urban Family Financial Management towards of a sakinah family in Semarang City - Ali Maskur; Khoirotin Nisa’; Munif Kolifah Sulistiyoningrum; Fajri Zulia Ramdhani; Nazar Nurdin; Najichah Najichah (Universitas Negeri Semarang, 2025)
This study examines how the sakinah family criteria, which include a peaceful and prosperous family, are achieved. Specifically, it examines whether families have a strong economic foundation to meet their needs and plan. It explores the shifting thoughts, behaviors, and investment strategies of urban residents who work as factory workers, private employees, teachers, and civil servants. The research focuses on the transition from a rural lifestyle, characterized by communal patterns like patembayan (a type of community based on shared bonds), gotong royong (cooperation), and strong kinship, to an urban one that prioritizes association and individualism. The research was conducted in the Bukit Beringin Timur residential area in Semarang City. The neighborhood’s location, surrounded by new industrial areas (Candi, Wijaya Kusuma, and Bukit Semarang Baru), reinforces this trend of individualism. The researchers employed the Asset-Based Community Development (ABCD) method to help the community understand its internal conditions and the potential for change. It was discovered that the shift from seasonal and agricultural income to consistent monthly salaries has fundamentally changed the mindset and behavior of urban communities. This is also reflected in their investment habits. Previously, investments were primarily focused on physical assets, such as agricultural land, plantations, and expensive gold jewelry. Now, residents are shifting to more accessible and affordable options, such as savings accounts, deposits, and gold bars, which can be paid in instalments. These new investments are primarily aimed at preparing for old age and retirement, rather than accumulating assets to be passed down to future generations.